In vitro immunomodulatory activity, cytotoxicity and chemistry of some central European polypores - Doskocil, Ivo; Havlik, Jaroslav; Verlotta, Roberta; Tauchen, Jan; Vesela, Lucia; Macakova, Katerina; Opletal, Lubomir; Kokoska, Ladislav; Rada, Vojtech (Pharmaceutical biology, 2016)
Context Some mushrooms of the order Polyporales are known for their immunomodulatory actions. Objective The objective of this study is to evaluate the in vitro phagocytic and cytotoxic effects of extracts from polyporales native to Central Europe. Materials and methods The effects of ethanol extracts from 27 polypore species on opsonized zymosan-induced phagocytosis of isolated human neutrophils were tested by a chemiluminescence method. Colon epithelial cell lines, Caco-2 and HT-29, were used for cytotoxicity assays, and extracts were chemically characterized in terms of total phenolic and β-glucan content. Results We observed phagocytosis or respiratory burst enhancing activity in 17 extracts, of which five species, namely Aurantiporus fissilis (Berk. & M.A. Curtis) H. Jahn ex Ryvarden, Trametes gibbosa (Pers.) Fr., Piptoporus betulinus (Bull.) P. Karst, Neolentinus lepideus (Fr.) Redhead & Ginns, Polyporus squamosus (Huds.) Fr., significantly increased phagocytosis in granulocytes by 205, 181, 158, 155 and 141%, respectively. The β-glucan content of the three most potent extracts was 58, 42 and 74 mg/g, respectively, and the polyphenol content was 155.6, 133.5 and 155.2 μmol of gallic acid equivalent/g, respectively. Some extracts showed cytotoxic activity, with higher cytotoxicity in Caco-2 than in HT-29 cells. Pycnoporus cinnabarinus (Jacq.) P. Karst. extract was cytotoxic to both cell lines, with IC50 values of 81 and 31 μg/mL, respectively. Discussion and conclusion The most promising extracts were from N. lepideus and Polyporus squamosus, which are edible species and may be considered safe. Our findings support their use as culinary preparations or food supplements for various immunological gut disorders.
Keywords: buňky HT-29; Immunologic Factors; viabilita buněk; Polyporales; protinádorové látky; beta-Glucans; Chemiluminescence; fagocytóza; Cell Survival; polyporales; fenoly; beta-glukany; mushrooms; lidé; colon cancer cell lines; Humans; Caco-2 Cells; granulocytes; HT29 Cells; Caco-2 buňky; Phagocytosis; Phenols; imunologické faktory; phagocytosis; Antineoplastic Agents